Contemporary treatment options for male hypogonadism - Paweł Sojka; Joanna Popiołek; Jakub Szczerba; Szymon Pokora; Agata Stefanowicz; Dominika Pokładnik; Katarzyna Jeleń; Karolina Pokora; Adam Podsiedlik; Alicja Poloczek (Journal of Education, Health and Sport, 2023)
Introduction